“Integration of Luqman’s Teachings in Character Building of Early Childhood: A Systematic Literature Review Approach” - Rina Syafridai; Nur Rochimah; Nancy Riana; Feronica Eka Putri (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025